Hyperoxic gassing with Tiron enhances bradykinin-induced endothelium-dependent and EDH-type relaxation through generation of hydrogen peroxide - Wong, Pui San; Roberts, Richard E.; Randall, Michael D. (Elsevier, 2015)
Oxygenation with 95%O2is routinely used in organ bath studies. However, hyperoxia may affect tissueresponses, particularly in studies which involve reactive oxygen species (ROS). Here, the effects of theantioxidant, Tiron, were investigated under different gassing conditions in the porcine isolated coronaryartery (PCA). Distal PCAs from male and female pigs were mounted in a wire myograph gassed witheither 95%O2/5%CO2or 95% air/5%CO2and pre-contracted with U46619. Concentration–response curvesto bradykinin were constructed in the presence of Tiron (1 mM), a cell permeable superoxide scavengerand catalase (1000 U ml−1) to breakdown H2O2. The H2O2level in Krebs’–Henseleit solution was detectedusing Amplex Red. Bradykinin produced concentration-dependent vasorelaxations in male and femalePCAs when gassed with either 95%O2or air, with no differences in the Rmaxor EC50. Tiron increased thepotency of bradykinin only when gassed with 95%O2in PCAs from both sexes. At 95%O2, catalase pre-vented the leftward shift caused by Tiron in both sexes indicating that catalase prevented the formationof H2O2by Tiron. In female PCAs, addition of catalase to Tiron significantly reduced the Rmax.In the EDH-type response (using L-NAME and indomethacin), Tiron enhanced the potency of the bradykinin-inducedvasorelaxation when gassed with 95%O2in PCAs from both sexes. Biochemical analysis using Amplex Reddemonstrated that H2O2was generated in Krebs’–Henseleit solution when gassed with 95%O2, but notwith air. Therefore, hyperoxic gassing conditions could alter the environment generating superoxidewithin the Krebs’–Henseleit buffer, which may, in turn, influence the in vitro pharmacological responses.